2000
DOI: 10.1086/308889
|View full text |Cite
|
Sign up to set email alerts
|

HST/STIS Ultraviolet Imaging of Polar Aurora on Ganymede

Abstract: We report new observations of the spectrum of Ganymede in the spectral range 1160È1720 made A with the Space Telescope Imaging Spectrograph (STIS) on the Hubble Space T elescope (HST ) on 1998 October 30. The observations were undertaken to locate the regions of the atomic oxygen emissions at 1304 and 1356 previously observed with the Goddard High Resolution Spectrograph on HST , that A , Hall et al. claimed indicated the presence of polar aurorae on Ganymede. The use of the 2A wide STIS slit, slightly wider t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
170
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 113 publications
(196 citation statements)
references
References 17 publications
24
170
2
Order By: Relevance
“…As a result the brighter Ly-α albedos of the contaminated (visible-darkened) regions could be explained by the surrounding region of purer water ice being relatively darker in the UV. The correlation of Europa's darker visible areas with UV bright regions is also consistent with the finding that Ganymede's darker visible surface has a slightly higher FUV albedo (J2%) than Europa (27).…”
Section: Data Processingsupporting
confidence: 87%
See 2 more Smart Citations
“…As a result the brighter Ly-α albedos of the contaminated (visible-darkened) regions could be explained by the surrounding region of purer water ice being relatively darker in the UV. The correlation of Europa's darker visible areas with UV bright regions is also consistent with the finding that Ganymede's darker visible surface has a slightly higher FUV albedo (J2%) than Europa (27).…”
Section: Data Processingsupporting
confidence: 87%
“…This mode has been previously used many times to observe the Galilean satellites (e.g., refs. [26][27][28][29] and more technical details are explained elsewhere (30). During each of the five orbits per visit two exposures with exposure times of 860 s (orbit 1) and 1,160 s (orbits 2-5) were obtained.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of emission in the ultraviolet lines of atomic oxygen were reported by Hall et al (1998) Feldman et al (2000) and are reproduced in Figure 1, which is taken from the above paper. A summary of the observations and exposure parameters may be found in Feldman et al (2000).…”
Section: Ultraviolet Auroramentioning
confidence: 95%
“…The ultraviolet aurora was discovered by Hall et al (1998) and observed in greater detail by Feldman et al (2000). Energetic electron data from the magnetosphere of Ganymede were obtained from the energetic particle detector (EPD) on board Galileo (Williams, Mauk, & McEntire 1997a ;Williams et al 1997b ;Williams & Mauk 1997 ;Paranicas et al 1999 ;Eviatar et al 2000).…”
Section: Introductionmentioning
confidence: 99%